Proceedings of the Fifth International Workshop on Computing Education Research Workshop 2009
DOI: 10.1145/1584322.1584336
|View full text |Cite
|
Sign up to set email alerts
|

A closer look at tracing, explaining and code writing skills in the novice programmer

Abstract: The way in which novice programmers learn to write code is of considerable interest to computing education researchers. One research approach to understanding how beginners acquire their programming abilities has been to look at student performance in exams. Lopez et al. (2008) analyzed student responses to an endof-first-semester exam. They found two types of questions accounted for 46% of the variance on the code writing portion of the same exam. One of those types of question required students to trace iter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(67 citation statements)
references
References 7 publications
4
62
1
Order By: Relevance
“…Research often reports that learners struggle with programming skills such as tracing [3,6] and understanding a model of the machine [2,9]. Having recognized this issue, other researchers [7,20] highlight the need for a defined hierarchy of programming skills. One study [16] attempted to provide such a hierarchy for objectoriented programming.…”
Section: Introductionmentioning
confidence: 99%
“…Research often reports that learners struggle with programming skills such as tracing [3,6] and understanding a model of the machine [2,9]. Having recognized this issue, other researchers [7,20] highlight the need for a defined hierarchy of programming skills. One study [16] attempted to provide such a hierarchy for objectoriented programming.…”
Section: Introductionmentioning
confidence: 99%
“…In the intermediate level is the ability to accurately read and trace code. At the top of the hierarchy is the ability to write non-trivial and correct code using programming constructs (Lopez et al, 2008;Sheard et al, 2008;Venables, Tan, & Lister, 2009). With this hierarchy in mind, each iteration of the BRACElet project specifies that examinations should comprise at least one instance of each of the three components detailed below:…”
Section: The Bracelet Projectmentioning
confidence: 99%
“…Therefore, our work supports the BRACElet notion of a hierarchical development of skills in learning to program. For a more detailed description of the analysis, see Venables et al (2009).…”
Section: Wearing the Assessment Bracelet: The Victoria University Expmentioning
confidence: 99%
“…Following this line of research, it was claimed that the skills constitute a hierarchy from Basics to Writing in [2] and Explain is an important precursor to acquire Writing. It was also reported that the result varies across universities in [3] and how they are related is not yet clear.…”
Section: Introductionmentioning
confidence: 98%